Expert Opinion Regarding Appropriately Timing Dermatological Surgeries in Patients With Recent Myocardial Infarctions. Issue 12 (December 2020) - McLawhorn, Justin M.; Imtiaz, Rasheen; Jasterzbski, Thomas; Stubblefield, Alexander; Chen, Sixia; Stasko, Thomas; Collins, Lindsey
Abstract : BACKGROUND: There is limited data on the risk of perioperative myocardial infarctions (MIs) in patients with a recent MI who undergo dermatologic surgeries. OBJECTIVE: Present the recommendations of dermatologic surgeons and cardiologists to determine the safety of dermatologic surgeries after a recent MI. METHODS: An electronic survey was distributed to Mohs surgeons and cardiologists to infer the risk of major adverse cardiac events (MACE) inherent to dermatologic surgery and determine timing of dermatologic surgery in patients with a recent MI. RESULTS: One hundred twenty Mohs surgeons and 30 cardiologists were surveyed. Ninety-seven percent of cardiologists and 87% of Mohs surgeons deemed cutaneous excisions and Mohs micrographic surgery as low-risk procedures with less than one-percent chance of MACE. Seventy-seven percent of cardiologists and 46% of Mohs surgeons stated dermatologic surgery should either not be delayed or be delayed up to 1 month after an MI. Responses between cardiologists and Mohs surgeons did not significantly differ. CONCLUSION: A preponderance of surveyed experts believe that most dermatologic surgeries may be safely performed in patients with a history of an MI within 1 month. The decision to implement urgent dermatologic surgery in patients with a recent MI should account for all clinically significant factors. Abstract : Supplemental Digital Content is Available in the Text.